2011
DOI: 10.1039/c0em00732c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of response of real-time SidePak AM510 monitor to secondhand smoke, other common indoor aerosols, and outdoor aerosol

Abstract: The amount of light scattered by airborne particles inside an aerosol photometer will vary not only with the mass concentration, but also with particle properties such as size, shape, and composition. This study conducted controlled experiments to compare the measurements of a real-time photometer, the SidePak AM510 monitor (SidePak), with gravimetric mass. PM sources tested were outdoor aerosols, and four indoor combustion sources: cigarettes, incense, wood chips, and toasting bread. The calibration factor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
84
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 36 publications
8
84
3
Order By: Relevance
“…Although the size range of secondhand smoke particles is 0.02-2 mm, about 90% of the particle mass is between 0.1 and 0.5 mm (Klepeis et al, 2003). Jiang et al (2011) found a consistent relationship between the SidePak readings and known mass concentrations of tobacco smoke measured using a gravimetric, pump-driven sampler with filters weighted on a precision laboratory scale.…”
Section: Instruments and Measurementsmentioning
confidence: 84%
See 4 more Smart Citations
“…Although the size range of secondhand smoke particles is 0.02-2 mm, about 90% of the particle mass is between 0.1 and 0.5 mm (Klepeis et al, 2003). Jiang et al (2011) found a consistent relationship between the SidePak readings and known mass concentrations of tobacco smoke measured using a gravimetric, pump-driven sampler with filters weighted on a precision laboratory scale.…”
Section: Instruments and Measurementsmentioning
confidence: 84%
“…Although the size range of secondhand smoke particles is 0.02-2 mm, about 90% of the particle mass is between 0.1 and 0.5 mm (Klepeis et al, 2003). Jiang et al (2011) found a consistent relationship between the SidePak readings and known mass concentrations of tobacco smoke measured using a gravimetric, pump-driven sampler with filters weighted on a precision laboratory scale.The calibration study by Jiang et al (2011) compared the SidePak monitor with gravimetric sampling for several types of aerosols: cigarette smoke, incense sticks, burning wood chips, toasted bread, and ambient air. The strong linear correlation between the gravimetric filter-based measurements and the SidePak monitor measurements gave R 2 values all above 0.995.…”
mentioning
confidence: 84%
See 3 more Smart Citations